Design and Test of Heat Absorption Using Heat Pipe Condenser for Patchouli Essential Destilazion - Daffa Alfarizi; Nasruddin A. Abdullah; Fazri Amir; Amalia Harmin (JURUTERA - Jurnal Umum Teknik Terapan, 2025)
This study aims to design and analyze a heat pipe condenser for heat absorption in the patchouli essential oil distillation process. The condenser was equipped with 6 heat pipes to condense patchouli essential vapor into liquid. In this design, the pan used is made of stainless steel with a capacity of 5 kg. In this study, a spiral copper pipe is also equipped to support heat absorption during the patchouli essential oil distillation process. In this study, several tests were carried out. the first without using a heat pipe, then a test equipped with a heat pipe, and the last using a heat pipe but not using water in a stainless steel pan. From the results of the study after the distillation of patchouli essential oil is as follows with testing without using a heat pipe on the condenser, the results of the absorption power were 840 J, and those using heat pipes had an absorption power of 42,924 J, and those using heat pipes but not using water in the pan had an absorption power of 39,900 J. Where in this study the heat pipe successfully absorbed heat power during the distillation process of patchouli essential oil.